Prepare to adapt: blood supply and transfusion support during the first 2 weeks of the 2019 novel coronavirus (COVID‐19) pandemic affecting Washington State. Issue 5 (27th April 2020) - Pagano, Monica B.; Hess, John R.; Tsang, Hamilton C.; Staley, Elizabeth; Gernsheimer, Terry; Sen, Nina; Clark, Christine; Nester, Theresa; Bailey, Curt; Alcorn, Kirsten
Abstract : BACKGROUND: The first coronavirus (COVID‐19) case was reported in United States in the state of Washington, approximately 3 months after the outbreak in Wuhan, China. Three weeks later, the US federal government declared the pandemic a national emergency. The number of confirmed COVID‐19 positive cases increased rather rapidly and changed routine daily activities of the community. STUDY DESIGN AND METHODS: This brief report describes the response from the hospital, the regional blood center, and the hospital‐based transfusion services to the events that took place in the community during the initial phases of the pandemic. RESULTS: In Washington State, the first week of March started with four confirmed cases and ended with 150; by the end of the second week of March there were more than 700 cases of confirmed COVID‐19. During the first week, blood donations dropped significantly. Blood units provided from blood centers of nonaffected areas of the country helped keep inventory stable and allow for routine hospital operations. The hospital‐based transfusion service began prospective triaging of blood orders to monitor and prioritize blood usage. In the second week, blood donations recovered, and the hospital postponed elective procedures to ensure staff and personal protective equipment were appropriate for the care of critical patients. CONCLUSION: As community activities are disrupted and hospital activities switch from routine operations to pandemic focused and urgent care oriented, the blood supply and usage requires a number of transformations.